2014
DOI: 10.1111/codi.12673
|View full text |Cite
|
Sign up to set email alerts
|

Rectal obliteration following stapled haemorrhoidopexy: a new endoscopic approach to restore luminal continuity

Abstract: 4 Almoudaris AM, Burns EM, Bottle A, Aylin P, Darzi A, Faiz O. A colorectal perspective on voluntary submission of outcome data to clinical registries. Br J Surg 2011; 98: 132-9. 5 Raftery J, Roderick P, Stevens A. Potential use of routine databases in health technology assessment. Heal Technol Assess 2005; 9: 1-92.We would like to thank Dr Dahlia AA Hawezy and Robyn Boyle who designed and drawn diagram of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Several papers described the safety and feasibility of the stapled hemorrhoidopexy and the good short-term results about shorter length of hospital stay, time until return to work, and high patient satisfaction due to the absence of perianal wounds that makes the procedure less painful than conventional hemorrhoidectomy [15][16][17][18][19][20]. Although it has these short-term benefits, the disadvantages of this technique seem to be some serious complications [9][10][11][12][13] and the higher recurrence rate at long-term follow-up than conventional hemorrhoidectomy. A recent meta-analysis reported a recurrence rate of 7.5 % after stapled procedure that was significantly higher than recurrence rate of 1.2 % after hemorrhoidectomy [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several papers described the safety and feasibility of the stapled hemorrhoidopexy and the good short-term results about shorter length of hospital stay, time until return to work, and high patient satisfaction due to the absence of perianal wounds that makes the procedure less painful than conventional hemorrhoidectomy [15][16][17][18][19][20]. Although it has these short-term benefits, the disadvantages of this technique seem to be some serious complications [9][10][11][12][13] and the higher recurrence rate at long-term follow-up than conventional hemorrhoidectomy. A recent meta-analysis reported a recurrence rate of 7.5 % after stapled procedure that was significantly higher than recurrence rate of 1.2 % after hemorrhoidectomy [19].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with excisional hemorrhoidectomy, stapled hemorrhoidopexy is more favorable in terms of postoperative discomfort [2,3], shorter length of hospital stay, time until return to work, and high patient satisfaction [4,5]. However, stapled procedure seems to be associated with some disadvantages as high recurrence rate (range 0-26 %) [6][7][8] and postoperative complications [9][10][11][12]. A recent retrospective multicenter study identified the criticism in the use of the conventional staplers reporting some serious complications as hematoma, bleeding, rectovaginal fistula, sepsis or perineal necrosis, important anastomotic defects, and closing up of rectum with stapler [13].…”
Section: Introductionmentioning
confidence: 99%